PHOTOLUMINESCENCE OBSERVATIONS OF DONOR-ACCEPTOR EMISSION IN MILLED Cd0.3Zn0.7Se NANOCRYSTALS (FUDMA JOURNAL OF SCIENCES, 2020)
Defects and impurities that arise during material synthesis are detrimental to device performance. Hence, an effective characterization tool is fundamental to effectively quantify and understand the origin of such defects. In this paper, we examine photoluminescence spectra (PL) from (650-900) nm of mechanically alloyed Cd0.3Zn0.7Se nanocrystals and observe three prominent emission peaks (1.4, 1.8, and 1.54) eV. The peaks were pinned at a fixed position despite a decrease in crystallites size which ought to increase the energy bandgap. The intensity of the peaks increases with milling time due to longer milling time which gives rise to a higher density of intrinsic defects. This was attributed to continuous deformations from the milling process. The formation energies of acceptor and donor defects remain constant to the conduction and valance band edge
Keywords: : Mechanical alloying, Photoluminescence spectra (PL), Donor-acceptor pairs (DAP), defects